Niveles de inteligencia emocional en estudiantes de quinto año de secundaria de colegios mixtos y diferenciados del Callao - Rosas Tavares, Norma Lidia (2010)
The present study had as intention verify if differences exist in the levels of Emotional Intelligence between students of mixed and differentiated colleges (only for males or only for ladies). The participants were 160 pupils of colleges mixed and differentiated from 3 districts of the Callao, both state and parochial constituting a sample probabilistic for a descriptive comparative study. The applied instrument was the Inventory of Baron's Emotional Intelligence for children and teenagers adapted by Nelly Ugarriza in 2004. The obtained results showed that yes significant differences exist in the levels of development of Emotional Intelligence between these two groups of students, being the highest levels in the students of mixed colleges. This verifies the hypothesis raised for this investigation that it was postulating that the system of education compound or coeducation, it contributes certain conditions and possibilities that favor a major emotional development of the pupils who take part of him.